Droplet-based lab-on-chip platform integrated with laser ablated graphene heaters to synthesize gold nanoparticles for electrochemical sensing and fuel cell applications - Sangam Srikanth (Nature Portfolio, 2021)
Abstract Controlled, stable and uniform temperature environment with quick response are crucial needs for many lab-on-chip (LOC) applications requiring thermal management. Laser Induced Graphene (LIG) heater is one such mechanism capable of maintaining a wide range of steady state temperature. LIG heaters are thin, flexible, and inexpensive and can be fabricated easily in different geometric configurations. In this perspective, herein, the electro-thermal performance of the LIG heater has been examined for different laser power values and scanning speeds. The experimented laser ablated patterns exhibited varying electrical conductivity corresponding to different combinations of power and speed of the laser. The conductivity of the pattern can be tailored by tuning the parameters which exhibit, a wide range of temperatures making them suitable for diverse lab-on-chip applications. A maximum temperature of 589 °C was observed for a combination of 15% laser power and 5.5% scanning speed. A LOC platform was realized by integrating the developed LIG heaters with a droplet-based microfluidic device. The performance of this LOC platform was analyzed for effective use of LIG heaters to synthesize Gold nanoparticles (GNP). Finally, the functionality of the synthesized GNPs was validated by utilizing them as catalyst in enzymatic glucose biofuel cell and in electrochemical applications.